1991
DOI: 10.1002/ajim.4700190309
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiologic study of cancer and other causes of mortality in San Francisco firefighters

Abstract: To test the hypothesis that firefighter exposures may increase cancer risk, mortality rates were calculated for 3,066 San Francisco Fire Department firefighters employed between 1940 and 1970. Vital status was ascertained through 1982, and observed and expected rates, rate ratios (RR), and 95% confidence intervals (CI) were computed using United States death rates for comparison. The total number deceased (1,186) was less than expected and there were fewer cancer deaths than expected. However, there were signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 36 publications
4
40
0
Order By: Relevance
“…Consistent with the results from other cohort studies [Beaumont et al, 1991;Demers et al, 1992;Guidotti, 1993;Tornling et al, 1994;Baris et al, 2001], we found significant decreases in mortality from infectious, allergic/endocrine, circulatory system, respiratory, digestive, and genitourinary diseases, and from external causes. We did not find an increased mortality from cardiovascular or respiratory disease.…”
Section: Non-cancer Mortalitysupporting
confidence: 92%
“…Consistent with the results from other cohort studies [Beaumont et al, 1991;Demers et al, 1992;Guidotti, 1993;Tornling et al, 1994;Baris et al, 2001], we found significant decreases in mortality from infectious, allergic/endocrine, circulatory system, respiratory, digestive, and genitourinary diseases, and from external causes. We did not find an increased mortality from cardiovascular or respiratory disease.…”
Section: Non-cancer Mortalitysupporting
confidence: 92%
“…In addition to potentially elevated risk of cardiovascular disease-related death, many studies have reported an elevated risk of several types of cancer among the firefighting population (7,21,38,40,41,54). The most common forms of cancer identified include thyroid cancer, breast, brain, prostate, esophageal, and lung cancer.…”
Section: Occupational Risk Factorsmentioning
confidence: 99%
“…One study from Denmark (46), in which the comparison population is unusual, reported a standardized mortality ratio of 317 for older firefighters, whereas studies on cohorts from San Francisco and Buffalo showed no excess (13,122). The possibility that an association is obscured, in comparison to the general population by the healthy worker effect, is probably less likely for this cause of death than for other chronic diseases; over the long periods of observation typical for these studies, the mortality experience of initially selected workers can be expected to approach that of the general population more closely, especially for noncar diovascular causes of death.…”
Section: Cancermentioning
confidence: 99%
“…Recent studies suggest that mortality is about that expected (13,27,44,46,96,122), although some studies have suggested elevations of 50% (99). There is ergonomic evidence that some firefighters may be stressed to the limit during the exertions of their work.…”
Section: Cardiovascular Diseasementioning
confidence: 99%